Analisis Prosedur Inventarisasi Barang Milik Daerah Berdasarkan Permendagri Nomor 47 Tahun 2021 Pada Badan Perencanaan Pembangunan Daerah Provinsi Sulawesi Utara - Mukhairah; David P.E. Saerang; Stanley Kho Walandouw (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
Inventory is an activity to collect data, record, and report the results of data collection of Regional Property (Permendagri 47/2021). Inventory is carried out so that the availability of Regional Property data is good in an effort to realize administrative order and physical order and facilitate the implementation of Regional Property management. This study aims to 1) determine the implementation of Regional Property inventory procedures in the process of data collection, recording, and reporting the results of data collection of Regional Property at the Regional Development Planning Agency of North Sulawesi Province; 2) determine the implementation of Regional Property inventory procedures in the process of data collection, recording, and reporting the results of data collection of Regional Property in accordance with Permendagri Number 47 of 2021. This type of research is qualitative research with a descriptive approach. The results showed that the Regional Property inventory procedure carried out at the BAPPEDA of North Sulawesi Province was in accordance with Permendagri Number 47 of 2021 concerning Procedures for Implementing Bookkeeping, Inventory, and Reporting of Regional Property. However, there are obstacles that often occur, namely obstacles in data entry due to the SIMDA BMD application which has not accommodated all Permendagri No.47 of 2021 so that it can hinder the BMD data entry process.